On the Reliability of Sodium Co-Intercalation in Expanded Graphite Prepared by Different Methods as Anodes for Sodium-Ion Batteries. Issue 14 (1st January 2017) - Cabello, Marta; Bai, Xue; Chyrka, Taras; Ortiz, Gregorio F.; Lavela, Pedro; Alcántara, Ricardo; Tirado, José L.
Abstract : Recent improvements of sodium ion batteries have been achieved by the use of graphitic carbon as an anode and glyme-based electrolytes. In this work, expanded graphites are prepared by thermal expansion, Broddie and Hummer's modified methods. Their structural, morphological and electrochemical properties are compared with those of the original natural graphite. XRD patterns, XPS and Raman spectra corroborate the presence of graphite oxide intermediates and reveal different reduced forms of expanded graphite which can affect the sodium insertion properties. The use of sodium triflate in diglyme enhanced the electrochemical performance in terms of delivering a flat plateau at ca. 0.65 and 0.55 V in discharge/charge cycles. The thermally expanded graphite increased the capacity and efficiency from 100 to 115 mA h g −1 and from 93 to 96% over 100 cycles when cycled at C rate as compared to natural graphite. Ex-situ XRD patterns reveal the presence of new set of reflections ascribable to sodium ordering in different stages as evidenced by the calculated Patterson diagrams. The new results described here would account for development of carbon-based material and their prospects and challenges for sodium ion battery anodes.